2003
DOI: 10.2741/1032
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosation of cysteine and reduced glutathione by nitrite at physiological pH

Abstract: Unlike the formation of nitrosothiols by nitrous acid, our study revealed that NO2- effectively reacted with L-cysteine or reduced glutathione (GSH) at pH 7.0 and 7.4, to form orange-pink products of S-nitrosocysteine (CySNO) or S-nitrosoglutathione (GSNO). The reactions were in a concentration-dependent manner. These products exhibited not only peak absorbances at around 340 and 540 nm, but also unique colors and patterns of mobility on cellulose thin layer chromatographic plates. In comparison, the S-nitrosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Burg et al (2002a) have reported on the synthesis of peptidomimetic GSH-conjugate analogues that are effective inhibitors of multidrug resistance protein 1 (MRP1) and thus can have a role in anticancer drug resistance (Burg & Mulder, 2002b). Finally, nitric oxide derivatives (S-nitrosoglutathione) have been extensively investigated as antioxidants (Rigobello et al, 2002) and nitric oxide donors (Kuo et al, 2003). These last derivatives, as well as a number of GSH conjugates, can also occur in vivo and represent a useful system for the transport of chemically reactive metabolites of both autologous and exogenous origins (Baillie & Slatter, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Burg et al (2002a) have reported on the synthesis of peptidomimetic GSH-conjugate analogues that are effective inhibitors of multidrug resistance protein 1 (MRP1) and thus can have a role in anticancer drug resistance (Burg & Mulder, 2002b). Finally, nitric oxide derivatives (S-nitrosoglutathione) have been extensively investigated as antioxidants (Rigobello et al, 2002) and nitric oxide donors (Kuo et al, 2003). These last derivatives, as well as a number of GSH conjugates, can also occur in vivo and represent a useful system for the transport of chemically reactive metabolites of both autologous and exogenous origins (Baillie & Slatter, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Western blotting was performed to evaluate the sensitivity and specificity of commercial rabbit anti-nitrosolysine or rat anti-nitrosohistidine (0.2µg/ml) after SDS-PAGE. The step of transferring required precooled tank buffer and prefrozen Towbin transfer buffer (5,11). Anti-rabbit IgG-AP conjugate or anti-rat IgG-AP conjugate (0.1 µg/ml) was used as the secondary antibody.…”
Section: Analysis By Sds-page and Western Blottingmentioning
confidence: 99%
“…Subsequently, PN can modify peptides/proteins in different ways. In addition to its tyrosine-nitration (1,(4)(5)(6)(7)(8)(9) and S-nitrosation of thiols (1,4,5,(9)(10)(11)(12), N-nitrosation of side chains (9,12,13) may also occur. The first indirect evidence of N-nitrosation was extracted via the observation that preincubation of poly basic amino acids with PN resulted in the significant alteration of UV spectra (12).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, nitrite can be easily protonated to form nitrous acid in extremely acidic conditions (pH < 3), and thus nitrosates thiols (3,50). Surprisingly, regardless of less intensive reactions, Snitrosation of thiols by nitrite may occur at neutral or physiological pH (15,51). Both NO and PN are short-lived, but their metabolites, nitrite and nitrate, are more stable.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that the effects of PN/nitrite/nitrate are not necessarily always harmful. Instead, their actions with appropriate timing, sites and intensity could be beneficial, such as the direct and indirect involvement of PN and nitroso-thiols in the signalling process that could relay the effects of NO (15,49,(51)(52)(53). Despite the remarkable progress in the research of tyrosine-nitration and thiolnitrosation (S-nitrosation) of proteins, the other types of nitrosation of proteins still remain unanswered.…”
Section: Introductionmentioning
confidence: 99%